PENGARUH NON PERFORMING FINANCING (NPF) DAN GROWTH OF GROSS DOMESTIC PRODUCT (GGDP) TERHADAP FINANCING TO DEPOSIT RATIO (FDR) DI PT BANK BNI SYARIAH PERIODE 2013-3017 - Qiny Shonia Az Zahra (Universitas Siliwangi, 2019)
Liquidity is an important point in banking operations as well as in the resilience and sustainability of a sharia bank. FDR at Bank BNI Syariah tends to decrease during the period 2013-2017. In addition, there is a phenomenon of a gap between the development NPF and GGDP against FDR in PT Bank BNI Syariah. This study has a purpose to know the partial influence of NPF and GGDP on FDR. In addition, this study aims to determine how much the simultan influence of NPF and GGDP on FDR.In some opinions and research results found by other researchers that NPF, and GGDP will affect FDR. GGDP increase, FDR will also increase, and vice versa. Whereas when the NPF increases, the FDR will decrease.The research method used is descriptive analytical verification by a quantitative approach. The data used is secondary data in the form of financial statements published by PT Bank BNI Syariah during the 2013-2017. Data analysis techniques used were linear regression, PPM correlation, coefficient of determination, and hypothesis testing (t test and F test) using SPSS 22.0.The conclusion obtained from this study that partially NPF has a significant effect on FDR with a determination coefficient of 56.7% and GGDP has no significant effect on FDR with a coefficient of determination of 0.2%. While simultaneously NPF and GGDP affect FDR with a coefficient of determination of 60.7%. In addition, it was found that the value of F calculated ≥ value of Ftable (12,374 3,630). This means that the estimated regression model is appropriate to explain the influence of NPF and GGDP on FDR at PT Bank BNI Syariah for the 2013-2017 period.